非小细胞肺癌T790M基因突变研究进展 (Zhongguo Fei Ai Za Zhi, 2013)
Patients with advanced non-small cell lung cancer (NSCLC) carrying epidermal growth factor receptor (EGFR) activating mutations benefit from EGFR-tyrosine kinase inhibitor (TKI) treatment, however, most of TKI-treated patients eventually suffer drug resistant after 10-month treatments. Previous studies demonstrated that T790M mutation in exon 20 of EGFR gene would be the essential factor leading to EGFR-TKI resistance, leaving the mechanisms of which elucidative. Current research identified that T790M is an independent, favorable prognostic factor for predicting survival, but whether it is also a predictive biomarker for EGFR-TKI efficacy is still controversial. Up to date, techniques to detect T790M mutation in lung cancer have been greatly improved and the new therapeutic strategies emerged as well. In this review, we summarized the newly updated data about T790M mutation in terms of its mechanisms involved in EGFR-TKI resistant, clinical value, advanced detection assays and ongoing strategies against the mutation subtype.